A Novel Design of Rescue Capsule considering the Pressure Characteristics and Thermal Dynamic Response with Thermomechanical Coupling Action Subjected to Gas Explosion Load - Xiaowei Zhai; Shibo Wu; Kai Wang; Xiaokun Chen; Haitao Li (Shock and Vibration)
To ensure the structural safety and reliability of coal mine rescue capsule in disastrous surroundings after gas explosion, in this paper, the thermomechanical coupling effect on a certain structure subjected to gas explosion was analyzed, and then a novel rescue capsule with a combination of radius and square features was designed according to the underground surroundings and relevant regulations on mine rescue devices. Foremost, the coupling mechanism of thermal-fluid-solid interaction between gas explosion shock wave and rescue capsule and the thermal dynamic response of the capsule subjected to explosion load of gas/air mixture was investigated and revealed by employing LS-DYNA. The variation laws and characteristics of stress field, displacement field, and temperature field of the capsule were analyzed based on the simulation results. Results show that the structural safety, tightness, and reliability of the capsule meet the requirements of the national safety regulations. The design method presented in this work provides a new thought for design of coal mine rescue capsule.